PERAN MAGNETIC RESONANCE IMGAGING DALAM DIAGNOSIS DAN PROGNOSIS CEDERA MEDULA SPINALIS AKUT - Reyhan Eddy Yunus,* Taufik Budianto,* Trifonia Pingkan Siregar,* Thariqah Salamah,* Ramdinal Aviesen (Neurona Majalah Kedokteran Neuro Sains, 2020)
CORD INJURY IS A COMMON TYPE OF INJURY THAT CAN BE HIGHLY FATAL CLINICALLY SPINAL CORD INJURY CAN BE ASSESSED USING STANDARDIZED PHYSICAL EXAMINATION SCORING FROM INTERNATIONAL STANDARDS FOR NEUROLOGICAL AND FUNCTIONAL CLASSIFICATION OF SPINAL CORD INJURY PATIENTS WHICH IS THE AMERICAN SPINAL INJURY ASSOCIATION ASIA IMPAIRMENT SCALE OR OFTEN CALLED AS AIS THE RESULTS OF THIS SCORING WILL THEN BE COMBINED WITH MAGNETIC RESONANCE IMAGING MRIEXAMINATION TO DETERMINE THE DIAGNOSIS AND PROGNOSIS